DEVELOPMENT OF TEACHING MATERIALS BASED ON POE MODEL TO IMPROVE STUDENTS' COMBINATORIAL THINKING SKILLS WITH A SIMPLE COMPUTER SECURITY CONTEXT - Jasmine Fajria Putri Noor; Tita Khalis Maryati; M. Hafiz (Math Educa Journal, 2025)
The ability to think combinatorially is the ability to find solutions to problems in the form of arranging combinations that may be used, which requires a continuous process of critical thinking and reasoning. This research aims to develop a mathematics teaching module on probability material based on the POE (Predict, Observe, Explain) learning model with a simple computer security context to facilitate student’s combinatorial thinking abilities. The development of teaching module uses the ADDIE development model, namely: Analysis, Design, Development, Implementation, and Evaluation. Data collection and analysis techniques in this research took the form of validation sheets by experts and student response questionnaires, as well as combinatorial thinking ability test instruments. The test instrument includes 5 main indicators of combinatorial thinking ability, which are tested to 25 students of class XII IPS 1 SMA Negeri 3 Depok. The results of this research state that the teaching module can facilitate student’s combinatorial thinking abilities. The teaching module is also included the the very feasible category based on the validation by experts and receiving positive responses from students.